2023
DOI: 10.1111/ene.15815
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammatory neuropathies and their impact on activities and participation

Abstract: Background: Chronic inflammatory demyelinating polyneuropathy (CIDP) and multifocal motor neuropathy (MMN) are inflammatory neuropathies that can lead to considerable limitations in daily activities and in social participation. However, systematic evaluation of these self-reported limitations is lacking in the currently available studies. Understanding the impact of these diagnoses on patients' life is important to optimize management strategies.Aim: To systematically assess the self-reported limitations in ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…A study on CIDP patients confirmed substantial limitations in mobility-related activities [5]. According to the current guidelines, orthoses, physiotherapy, and occupational therapy are recommended for CIDP patients [9].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A study on CIDP patients confirmed substantial limitations in mobility-related activities [5]. According to the current guidelines, orthoses, physiotherapy, and occupational therapy are recommended for CIDP patients [9].…”
Section: Discussionmentioning
confidence: 95%
“…In neuromuscular disorders muscle weakness often results in gait abnormalities, leading to reduced walking distance, increased fatigue, and a high risk of falls [5,6]. This restricted mobility may also contribute to weight gain, exacerbating motor function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the clinical scales and even patient reported outcome measures (e.g., Medical Research Council (MRC) scale, handgrip strength, and Rasch-built Overall Disability Score (RODS)) do not necessarily correspond with patients' own perspectives on experienced disease burden and impact on participation (work and social interaction). 5 In this issue of the journal, Al-Zuhairy and Jakobsen reviewed the literature on published data on outcome in CIDP. 6 The authors focused on typical CIDP and excluded variants of CIDP.…”
mentioning
confidence: 99%